2014
DOI: 10.1371/journal.pone.0100335
|View full text |Cite
|
Sign up to set email alerts
|

Batch Effect Confounding Leads to Strong Bias in Performance Estimates Obtained by Cross-Validation

Abstract: BackgroundWith the large amount of biological data that is currently publicly available, many investigators combine multiple data sets to increase the sample size and potentially also the power of their analyses. However, technical differences (“batch effects”) as well as differences in sample composition between the data sets may significantly affect the ability to draw generalizable conclusions from such studies.FocusThe current study focuses on the construction of classifiers, and the use of cross-validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…A fundamental limitation of breast cancer outcome prediction is that it has proved very difficult to obtain a robust classifier performance across different datasets. It was found that, despite properly cross-validated classifier training, prediction performance decreases dramatically when a classifier trained on one dataset is applied to another one ( Lazar et al , 2013 ; Soneson et al , 2014 ). Moreover, the prognostic gene signatures identified using these classifiers have poor concordance across different studies ( Ein-Dor et al , 2005 ; van Vliet et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental limitation of breast cancer outcome prediction is that it has proved very difficult to obtain a robust classifier performance across different datasets. It was found that, despite properly cross-validated classifier training, prediction performance decreases dramatically when a classifier trained on one dataset is applied to another one ( Lazar et al , 2013 ; Soneson et al , 2014 ). Moreover, the prognostic gene signatures identified using these classifiers have poor concordance across different studies ( Ein-Dor et al , 2005 ; van Vliet et al , 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these datasets do not include MDS samples; therefore, they could not be used for the validation of our binary classifier. Combining these datasets with the MDS samples from other datasets could be problematic because of possible batch effects 71 . Also, the expression profile of 159 MDS cases in the GSE58831 dataset 72 could not be directly compared to the MDS samples analyzed in this study because of the difference in the tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This sample size supplies sufficient power for downstream analyses while minimizing the total number of animals sacrificed4445. We used Trizol (Life Technologies, Grand Island, NY) for extractions, following a modified version of the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%